From 2D to 3D: a facile and effective procedure for fabrication of planar CH3NH3PbI3 perovskite solar cells. Issue 37 (12th September 2018) - Zhang, Yu; Li, Fengzhu; Jiang, Ke-Jian; Huang, Jin-Hua; Wang, Huijia; Fan, Haochen; Wang, Pengcheng; Liu, Cai-Ming; Zhang, Li-Peng; Song, YanLin
Abstract : 2D organic–inorganic hybrid perovskite single crystal ( n -C3 H7 NH3 )6 Pb4 I14 was synthesized, and converted into 3D CH3 NH3 PbI3 perovskite via organic-cation displacement. Using the film as a light absorber, planar perovskite solar cells were fabricated with the best power conversion efficiency of 19.19%. Abstract : Herein, new organic–inorganic hybrid perovskite single crystals of complex1 with the formula of ( n -C3 H7 NH3 )6 Pb4 I14 are synthesized from an aqueous HI solution containing PbI2 and propylammonium iodide. The single crystal X-ray crystallographic study shows that the structure consists of two-dimensional (2D) sheets of corner- and face-sharing [Pb2 I7 ] 3− octahedra, and the inorganic layers are separated by layers of 3-propylammonium cations. The 2D perovskite material features good film formability upon simple solution deposition. This 2D phase can be easily converted into 3D CH3 NH3 PbI3 (MAPbI3 ) perovskite via an organic-cation displacement approach, exhibiting a compact, ultrasmooth, and textured morphology. Using the film as a light absorber, planar CH3 NH3 PbI3 perovskite solar cells are fabricated, and the best power conversion efficiency of 19.19% is obtained with good reproducibility.